If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9r-9r+9=-1-r
We move all terms to the left:
9r-9r+9-(-1-r)=0
We add all the numbers together, and all the variables
9r-9r-(-1r-1)+9=0
We add all the numbers together, and all the variables
-(-1r-1)+9=0
We get rid of parentheses
1r+1+9=0
We add all the numbers together, and all the variables
r+10=0
We move all terms containing r to the left, all other terms to the right
r=-10
| (2x+7)/3=8,7 | | -x-3+4+2x=9 | | 3k-2=-2-7k | | x÷3−7=2 | | 9+4x+1x=14 | | -7-6f=-5f | | 49×2=3a-10a | | -5p=6-4p | | O.5x=-4.5 | | -9w+2=10-10w | | -5.9=(h/5)+12.2 | | 11-7x2=-157 | | -9+b=7+4-4b | | 3x+6x/2=72 | | 5x2+41x+40=-2 | | 12(8c-4)=7c-7 | | -3c/10-31=83 | | 5q-7=2q+8 | | 3(c+4)-6c=2(4-2c) | | -2+6c=-10+5c | | 77=1x+7x+5 | | -15/4=5u | | 7.5=5x | | 17.5-10=5x | | -4y=-7y+6 | | 17.5=5x+10 | | 4x=(1+5-8) | | 2+2a=54 | | -6+3x=-39 | | 3y2-2×-6y=0 | | 2(4x-1)=26X= | | 3r-5+3=16 |